2013
DOI: 10.1073/pnas.1303302110
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic RAS pathway activation promotes resistance to anti-VEGF therapy through G-CSF–induced neutrophil recruitment

Abstract: Granulocyte-colony stimulating factor (G-CSF) promotes mobilization of CD11b + Gr1 + myeloid cells and has been implicated in resistance to anti-VEGF therapy in mouse models. High G-CSF production has been associated with a poor prognosis in cancer patients. Here we show that activation of the RAS/MEK/ERK pathway regulates G-CSF expression through the Ets transcription factor. Several growth factors induced G-CSF expression by a MEK-dependent mechanism. Inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 47 publications
2
81
0
1
Order By: Relevance
“…These data suggest that simultaneous inhibition of neutrophils and anti-angiogenic therapy might be an effective anticancer strategy. Indeed, therapeutic synergy is observed when anti-VEGFA therapy is combined with depletion of neutrophils via anti-Gr1 or anti-G-CSF antibodies 179,181 .…”
Section: Combining Neutrophil Targeting With Other Anti-cancer Therapiesmentioning
confidence: 99%
“…These data suggest that simultaneous inhibition of neutrophils and anti-angiogenic therapy might be an effective anticancer strategy. Indeed, therapeutic synergy is observed when anti-VEGFA therapy is combined with depletion of neutrophils via anti-Gr1 or anti-G-CSF antibodies 179,181 .…”
Section: Combining Neutrophil Targeting With Other Anti-cancer Therapiesmentioning
confidence: 99%
“…PLR can occur in 10% to 15% of cancer patients and are strongly predictive of poor clinical outcomes (33,34). We have previously reported that activation of the oncogenic RAS/MEK/ERK pathway induces expression of G-CSF from tumor cells through the Ets transcription factor (37). Blockade of G-CSF release through MEK inhibition, antibody-mediated G-CSF neutralization, or targeted inactivation of the G-CSF receptor in mice, resulted in suppression of aberrant neutrophil accumulation and inhibition of tumor angiogenesis and metastasis (35,(37)(38)(39).…”
Section: Deregulation Of Neutrophils By the Tumor Microenvironmentmentioning
confidence: 99%
“…We have previously reported that activation of the oncogenic RAS/MEK/ERK pathway induces expression of G-CSF from tumor cells through the Ets transcription factor (37). Blockade of G-CSF release through MEK inhibition, antibody-mediated G-CSF neutralization, or targeted inactivation of the G-CSF receptor in mice, resulted in suppression of aberrant neutrophil accumulation and inhibition of tumor angiogenesis and metastasis (35,(37)(38)(39). The significance of tumor-derived GM-CSF or IL6 on neutrophil homeostasis in malignancies has been less extensively characterized.…”
Section: Deregulation Of Neutrophils By the Tumor Microenvironmentmentioning
confidence: 99%
“…Oncogenic pathways also influence the recruitment of inflammatory cells, which themselves may exhibit pro-angiogenic and pro-coagulant phenotypes [51,52]. For example, myeloid cells and monocytes could release TF-containing EVs (microparticles/MPs) [53], while neutrophils may deploy extracellular chromatin traps (NET-osis) [54], or participate in other events that could add to cancer-related coagulation perturbations.…”
mentioning
confidence: 99%